Machine Fabrication Student’s Self-Esteem and Interest in Career Choice as Correlates of their Entrepreneurial Intention in Nigerian Universities - AINETOR, Anthony U.; ILEVBARE, Martins (FUDMA Journal of Engineering and Technology, 2026)
The study seeks to establish the relationship between self-esteem and interest in career choice of machine fabrication students in Nigerian Universities and their entrepreneurial intention. Two hypotheses formulated were tested at 0.05 level of significance using two research questions. The study adopted a correlational research design. The population was 132 students that offer machine fabrication in eleven universities from South-South geopolitical zone of Nigeria. There was no sampling because of the manageable size. A questionnaire was administered to the students. The internal consistency of the questionnaire was determined using the Cronbach Alpha Reliability method. Self-esteem had a reliability coefficient of 0.84, interest had a reliability of 0.74 and entrepreneurial intention had a reliability of 0.89 and an overall reliability of instrument was 0.92. 130 copies were retrieved out of 132 copies administered. Pearson Product Moment Correlation method was used to analyze the data for answering research questions. Linear and Multiple Regression were used to test the hypotheses at 0.05 levels of significance. The findings showed that a negative and weak relationship exists between self-esteem, interest and entrepreneurial intention of students. There was no significant relationship between self-esteem, interest and entrepreneurial intention. The Lecturers and school authorities should improve the entrepreneurial intention of machine fabrication students in Nigerian Universities by organizing seminars and workshops was the key recommendation.